Comparison of protein sources for phase II starter diets - Hansen, J.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 432 weanling pigs (initially 15.3 lb and 21 d of age) was used in a growth trial to compare various protein sources in the Phase II starter diet. During Phase I (0 to 7 d post-weaning), all pigs were fed a common high nutrient density diet containing 1.5% lysine, 10% porcine plasma, 10% lactose, and 20% dried whey. During Phase II (7 to 28 d post-weaning), pigs were fed one of six experimental diets. All Phase II diets contained 10% dried whey and were formulated to 1.18% lysine. The positive control diet contained 4% menhaden fish meal (FISH). Synthetic amino acids were used to replace fish meal to form an ideal protein, negative control diet (AA). Spray-dried porcine plasma (SDPP), spray-dried blood meal (SDBM), soy protein concentrate (SPC), and extruded soy protein concentrate (ESPC) replaced fish meal on a lysine basis to form the other four diets. During the grower phase (28 to 56 d postweaning), all pigs were fed a common 1.1% lysine, milo-soybean meal diet. Average daily gain (lb), ADFI (lb), and F/G during Phase I were .39, .53, and 1.41, respectively. During Phase II, SPC and ESPC effectively replaced fish meal as a protein source; however, pigs fed diets containing the spray-dried blood products (SDPP or SDBM) gained faster than pigs fed the other four diets. Pigs fed the diet containing synthetic amino acids had poorer feed conversion than pigs fed diets containing the intact protein sources. Pigs fed the diet containing SDBM during Phase II gained faster during the subsequent grower phase than pigs fed the other diets. Based on these results and earlier research, optimal staging of starter diets includes using SDPP in Phase I and SDPP or SDBM in Phase II.
Keywords: Starter; Performance; By-products; Protein; Sources